Research hotspots and trends between open education and vocational education - Yang, You; Rasul, Mohamad Sattar; Omar, Marlissa (Journal of Education and Learning (EduLearn), 2025)
Open education and vocational education are crucial for building a learning society and promoting national development. This study uses CiteSpace software to conduct an in-depth analysis of keywords visual timelines for research hotspots, and keywords with the strongest citation bursts in China and other countries. Given the rapid global development of open and vocational education, it is essential for policymakers, educators, and researchers to stay abreast of emerging trends and critical areas to formulate and implement effective educational policies and strategies. Therefore, analyzing these research hotspots and trends holds significant importance. The results indicate that in China, the integration and development of open and vocational education are key trends, with a strong emphasis on coordinated development and innovative educational models. In other countries, the focus shifts towards enhancing adult learners' vocational skills and online learning capabilities. These insights offer concrete guidance for resource allocation, curriculum development, and future research directions. They assist policymakers in optimizing resource distribution, educators in creating innovative curricula, and researchers in identifying new research areas. Thus, this comprehensive understanding of the dynamic evolution of open and vocational education can lead to more effective educational practices and policies worldwide.